Species–environment interactions changed by introduced herbivores in an oceanic high-mountain ecosystem. Issue 1 (5th January 2017) - Seguí, Jaume; López-Darias, Marta; Pérez, Antonio J.; Nogales, Manuel; Traveset, Anna
Abstract : We studied the fitness of an endemic and vulnerable violet species along its altitudinal range (2, 400 m - 3, 500 m), and we found it to be mainly affected by inter-annual and microhabitat variability along the gradient, especially at the lowest edge. Despite the increasingly adverse environmental conditions, the plant showed no pollen limitation with elevation, which is attributed to the increase in selfing and decrease in competition for pollinators at higher elevations. Plant fitness was extremely reduced owing to the presence of non-native rabbits, which changed plant trait-environment interactions along the gradient, threatening the survival of this violet. Abstract: Summit areas of oceanic islands constitute some of the most isolated ecosystems on earth, highly vulnerable to climate change and introduced species. Within the unique high-elevation communities of Tenerife (Canary Islands), reproductive success and thus the long-term survival of the species may depend on environmental suitability as well as threat by introduced herbivores. By experimentally modifying the endemic and vulnerable species Viola cheiranthifolia along its entire altitudinal occurrence range, we studied plant performance, autofertility, pollen limitation and visitation rate and the interactive effect of grazing by non-native rabbits on them. We assessed the grazing effects by recording (i) the proportion of consumed plants and flowers along the gradient, (ii) comparing fitness traits of herbivore-excluded plants along the gradient, and (iii) comparing fitness traits, autofertility and pollen limitation between plants excluded from herbivores with unexcluded plants at the same locality. Our results showed that V. cheiranthifolia performance is mainly affected by inter-annual and microhabitat variability along the gradient, especially in the lowest edge. Despite the increasingly adverse environmental conditions, the plant showed no pollen limitation with elevation, which is attributed to the increase in autofertility levels (≥ 50% of reproductive output) and decrease in competition for pollinators at higher elevations. Plant fitness is, however, extremely reduced owing to the presence of non-native rabbits in the area (consuming more than 75% of the individuals in some localities), which in turn change plant trait-environment interactions along the gradient. Taken together, these findings indicate that the elevational variation found on plant performance results from the combined action of non-native rabbits with the microhabitat variability, exerting intricate ecological influences that threaten the survival of this violet species.